A multicenter clinical study on parent-implemented early intervention for children with global developmental delay - Dong, Ping; Xu, Qiong; Zhang, Ying; Li, Dong-yun; Zhou, Bing-rui; Hu, Chun-chun; Liu, Chun-xue; Tang, Xin-rui; Fu, Shi-yun; Zhang, Lan; Li, Hai-feng; Jia, Fei-yong; et al. (Frontiers in Pediatrics, 2023)
Objective: Early identification and intervention for children with global developmental delay (GDD) can significantly improve their prognosis and reduce the possibility of developing intellectual disability in the future. This study aimed to explore the clinical effectiveness of a parent-implemented early intervention program (PIEIP) for GDD, providing a research basis for the extended application of this intervention strategy in the future. Methods: During the period between September 2019 and August 2020, children aged 3 to 6 months diagnosed with GDD were selected from each research center as the experimental group and the control group according to the voluntary principle of parents. For the experimental group, the PIEIP intervention was conducted for the parent-child pair. Mid-term and end-stage assessments were performed, respectively, at 12 and 24 months of age, and parenting stress surveys were completed. Results: The average age of the enrolled children was 4.56 ± 1.08 months for the experimental group (n = 153) and 4.50 ± 1.04 months for the control group (n = 153). The comparative analysis of the variation in the progress between the two groups by independent t-test showed that, after the experimental intervention, the developmental quotient (DQ) of locomotor, personal-social, and language, as well as the general quotient (GQ) of the Griffiths Mental Development Scale-Chinese (GDS-C), the children in the experimental group demonstrated higher progress than those in the control group (P<0.05). Furthermore, there was a significant decrease in the mean standard score of dysfunctional interaction, difficult children and the total level of parental stress in the term test for the experimental groups (P<0.001 for all). Conclusions: PIEIP intervention can significantly improve the developmental outcome and prognosis of children with GDD, especially in the areas of locomotor, personal-social, and language.